1995
DOI: 10.1149/1.2048464
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion in Supercritical Water Oxidation Systems: A Phenomenological Analysis

Abstract: Pronounced corrosion damage occurs in supercritical water oxidation reactors, and few materials are immune to attack. In this paper, we describe a phenomenological mode] for the corrosion process, and we discuss the effect of electrolyte dissociation and water density, as influenced by temperature and pressure, upon the kinetics of corrosion of metals and alloys in supercritical.water. The corrosion process at near-critical temperatures is believed to involve acid attack, with the concentration of H § being a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 3 publications
(4 reference statements)
2
49
0
2
Order By: Relevance
“…95 The main ones are elevated temperatures and high concentrations of dissolved oxygen, along with the extreme pH values, high concentrations of ionic species (at subcritical conditions), and sharp pressure changes.…”
Section: Corrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…95 The main ones are elevated temperatures and high concentrations of dissolved oxygen, along with the extreme pH values, high concentrations of ionic species (at subcritical conditions), and sharp pressure changes.…”
Section: Corrosionmentioning
confidence: 99%
“…Corrosion experiments in supercritical aqueous solutions show that the corrosion at supercritical temperatures of 500°C was lower by orders of magnitude than at subcritical temperatures of 300°C. 95,[97][98][99] This fact is explained by the sharp change of the thermophysical properties of water in the surroundings of the critical point such as density and dielectric constant.…”
Section: Corrosionmentioning
confidence: 99%
“…Electrochemical noise measurements will be employed to monitor corrosion processes that occur on metallic materials exposed to super critical water (SCW) [15,16]. A schematic of the electrochemical noise sensor is shown in Figure 11.…”
Section: Electrochemical Noise Sensormentioning
confidence: 99%
“…In the case of localized corrosion, the noise frequently arises from discrete events that can be related to the development of damage. In previous work in this laboratory, Macdonald et al [15] and Kriksunov and Macdonald [16] developed an ENS system based on a zero resistance ammeter (ZRA) coupled to a bandpass-filter/RMS (root-mean-squares) integrated circuit to monitor electrochemical noise on carbon steel and stainless steels in aqueous solutions at temperatures ranging from 200°C to 550°C. These studies demonstrated the viability of ENS for monitoring corrosion phenomena in high subcritical and supercritical aqueous systems, and confirmed the previous& observed maximal corrosion rate within the neighborhood of the critical temperature (350-400°C).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, supercritical CO2 has been used for various purposes, such as the recycling of precious metals [15], leaf oil extraction and quinone analysis, among others [16]. As SFT simultaneously uses extreme temperatures and pressures, consequently, chemical corrosion increases [17,18]. The corrosion of various types of materials under high temperature and pressure conditions has been investigated intensively [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%